ANTIOXIDANT EFFECT OF CATECHIN LOADED POLYMERIC NANOPARTICLE - Tuncer, Burcu; Mansuroglu, Banu; Derman, Serap (YILDIZ TECHNICAL UNIV, 2016)
Flavonoids are polyphenols compounds a structural class of mainly natural and a products of secondary metabolism of plants. Flavonoids, which can be found in herbs and trees, act as natural chemopreventives and anticancer agents [1]. As natural products, they have major importance for human life and also have a widespread effect such as antioxidant, antinflammatory, anticarcinogen, antidiabetic [2, 3]. However, bioavailability of this polyphenolic antioxidant have limited because of their high water solubility [4], low absorption, permeability, stability, slow dissolution rate, and light-induced decomposition over time in the physiological medium. In recent years, various methods have been tried to overcome the limitations of flavonoids, including its incorporation into micels and nanoparticles.
Keywords: Nanoparticle; catechin; antioxidant activity; polymeric nanoparticle; GREEN TEA CATECHINS; IN-VITRO; PLGA NANOPARTICLES; BIODEGRADABLE NANOPARTICLES; POLYPHENOLIC CATECHINS; CELLULAR UPTAKE; PARTICLE-SIZE; DRUG-RELEASE; BLACK TEA; VIVO; Engineering